2013
DOI: 10.1590/abd1806-4841.20131990
|View full text |Cite
|
Sign up to set email alerts
|

Severe Multi-Resistant Pemphigus vulgaris: prolonged remission with a single cycle of Rituximab

Abstract: Pemphigus vulgaris is an autoimmune bullous disease whose therapy is based on systemic corticosteroids, with or without immunosuppressants. Rituximab is a chimeric monoclonal antibody of the IgG class, directed at a specific CD20 B cell surface antigen, used in pemphigus vulgaris empirically since 2002, with success in 90% of the cases and long periods of remission. Male patient, 33 years old, diagnosed with pemphigus vulgaris, confirmed by histopathology and direct immunofluorescence. He was treated for seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In total, we recorded data of 155 pemphigus patients, 124 of whom had PV while 31 had PF patients with ages ranging from 4 to 86 years . There was no association between disease type and clinical outcomes, with 80% of both PV and PF patients achieving complete response ( P = 0.95).…”
Section: Resultsmentioning
confidence: 99%
“…In total, we recorded data of 155 pemphigus patients, 124 of whom had PV while 31 had PF patients with ages ranging from 4 to 86 years . There was no association between disease type and clinical outcomes, with 80% of both PV and PF patients achieving complete response ( P = 0.95).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, it has been shown that patients treated with rituximab earlier in the disease course may have better outcomes, enduring complete remission with no or minimal systemic therapy for 19 months (Lunardon et al, 2012[ 21 ]). Other studies also indicated that adjuvant rituximab therapy may hold promises in long-lasting treatment of severe recalcitrant PV with no or slight adverse drug-related events (Baum et al, 2013[ 4 ]; Behzad et al, 2012[ 5 ]; Cho et al, 2014[ 7 ]; Corral et al, 2013[ 9 ]; Craythorne et al, 2011[ 10 ]; El Tal et al, 2006[ 11 ]; Eming et al, 2008[ 12 ]).…”
Section: Discussionmentioning
confidence: 99%
“…11 In the last years, it has been considered the first-line option to treat pemphigus in developed countries. 1 Nevertheless, in Brazil, Rituximab has been prescribed as an exceptional option, for those cases of unresponsiveness to commoner drugs, 12 , 13 , 14 which encouraged us to look for a diverse treatment in order to decrease corticoid side effects when chronically prescribed. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%